Natural-origin bioadhesive hydrogel with dual antioxidative and immunoregulatory properties for enhanced angiogenesis and wound healing - Huiyang Li; Lifei Ma; Ni Zhu; Xiaoyu Liang; Kaijing Liu; Xue Fu; Chuangnian Zhang; Jing Yang (Bioactive Materials)
Effective wound repair is critically impaired by persistent inflammatory responses and oxidative damage, which collectively impede tissue regeneration and exacerbate fibrotic scarring. To overcome these dual barriers, we engineered a multifunctional hydrogel platform, designated KGM-GA/XG-DPA (KG-XDgel), through molecular integration of gallic acid-conjugated konjac glucomannan (KGM-GA) with dopamine-modified xanthan gum (XG-DPA). This biomaterial system demonstrates dual therapeutic modalities: (1) concurrent scavenging of reactive oxygen species (ROS) via synergistic redox activity from phenolic components (gallic acid and catechol moieties), and (2) targeted immunomodulation through carbohydrate-mediated engagement of CD206 receptors to drive M2 macrophage polarization. Enhanced by dopamine-driven tissue adhesion and self-healing properties, the hydrogel maintains structural integrity under physiological stress. In murine full-thickness wound models, KG-XDgel treatment achieved an impressive 81 % epithelial closure within 7 days, accompanied by an 8.7-fold upregulation of CD31+ neovascular networks by day 14. Notably, these therapeutic outcomes were accomplished through endogenous biological activation rather than exogenous growth factors or pharmacological agents. By converging antioxidant defense with innate immune reprogramming in a single biomaterial platform, KG-XDgel establishes a novel drug-free paradigm for accelerated wound regeneration, demonstrating significant translational potential in clinical wound management.